Molecular Basis of Class B GPCR Selectivity for the Neuropeptides PACAP and VIP - Liao, Chenyi; Remington, Jacob M.; May, Victor; Li, Jianing (Frontiers in Molecular Biosciences, 2021)
The related neuropeptides PACAP and VIP, and their shared PAC1, VPAC1 and VPAC2 receptors, regulate a large array of physiological activities in the central and peripheral nervous systems. However, the lack of comparative and molecular mechanistic investigations hinder further understanding of their preferred binding selectivity and function. PACAP and VIP have comparable affinity at the VPAC1 and VPAC2 receptor, but PACAP is 400-1000 fold more potent than VIP at the PAC1 receptor. A molecular understanding of the differing neuropeptide-receptor interactions and the details underlying the receptor transitions leading to receptor activation are much needed for the rational design of selective ligands. To these ends, we have combined structural information and advanced simulation techniques to study PACAP/VIP binding selectivity, full-length receptor conformation ensembles and transitions of the PACAP/VIP receptor variants and subtypes, and a few key interactions in the orthosteric-binding pocket. Our results reveal differential peptide-receptor interactions (at the atomistic detail) important for PAC1, VPAC1 and VPAC2 receptor ligand selectivity. Using microsecond-long molecular dynamics simulations and the Markov State Models, we have also identified diverse receptor conformational ensembles and microstate transition paths for each receptor, the potential mechanisms underlying receptor open and closed states, and the interactions and dynamics at the transmembrane orthosteric pocket for receptor activation. These analyses reveal important features in class B GPCR structure-dynamics-function relationships, which provide novel insights for structure-based drug discovery.